A rare complication after local tonsillectomy (pulmonary atelectasis) - Elçin Aygün; Bayram Uğurlu; Fatih Evcimik; Emre Özkurt; Tarık Şapçı (Turkish Archives of Otorhinolaryngology, 2007)

(untitled)
The complications of tonsillectomy are most common due to the surgical procedures or the anesthetic managements. The anatomic localization and the potential complications of the surgical procedure shall keep the surgeons away from underestimation. Local tonsillectomy is usually preferred as it is performed in a short time and as it has minimum risk carried out with anesthetic management. Serious complications can rarely be seen after local tonsillectomy. In this case unilateral pulmonary atelectasis was the result of the coagulum that obstructed the airway. It was diagnosed and treated medically and the patient was discharged without any complication.